Hubungan Karakteristik Individu dan Beban Kerja Fisik dengan Kejadian Musculoskeletal Disorders (MSDs) pada Pekerja Proyek Pembangunan Makam PT X - Adinda Gita Savana Firdausa; Ekawati Ekawati; Siswi Jayanti (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Background: Occupational Safety and Health (OHS) is essential in creating a safe and productive work environment, as well as complying with government regulations. One of the main risks in the workplace is musculoskeletal disorders (MSDs). This study aims to analyze the factors of individual characteristics such as age, gender, length of service, and physical load with the incidence of musculoskeletal disorders in the PT X tomb construction project. Methods: This research is a quantitative study using a cross-sectional design. The population of this study were all workers of the PT X tomb construction project totaling 30 people so that the sample was obtained using a total sampling technique of 30 workers. Data were obtained from observations of the work environment and work process to determine physical workload based on SNI 7269:2009, interviews on age, gender, and length of service, and measurement of MSDs levels with the Nordic Body Map (NBM) questionnaire. Data processing techniques using chi-square Test with Fisher Exact Test. Results: Most workers are > 35 years old (Old Age) as much as 70%, male as much as 80%, have a work period of > 10 years as much as 43.3%, and have a heavy physical workload as much as 53.3%. The results of this study found that 36,7% of PT X tomb construction project workers experienced MSDs complaints in the high category. The results showed a relationship between age (0.025), gender (0.001), tenure (0.001), and physical workload (0.003) with the incidence of musculoskeletal disorders. Conclusions: From the research results, it was concluded that there is a relationship between age, gender, length of service, and physical workload with the incidence of musculoskeletal disorders in the PT X cemetery construction project.